Pembelajaran Luas Daerah Persegi Panjang Berdasarkan Standar Pengajaran National Council of Teachers of Mathematics (NCTM) Untuk Meningkatkan Pemahaman Siswa Kelas III SDN Dinoyo I Malang - Sulistiani, Ika Ratih (UIN Sunan Kalijaga Yogyakarta, 2012)
This research is analyzing the problem that faced by students of SD Negeri 1 Dinoyo Malang inÂ difficulty of understanding rectangle area. According to the discussion with their teacher, it is found that the learning still not gives more chance to the students to find out the concept of rectangle area with their own ways. Moreover, some students are difficult in solving daily problem containing model of rectangle area. Therefore it needs great effort to build students understanding on the concept of rectangle area. One of effort that teacher can do is trying to apply the learning based on process standard NCTM. The aim of this research is to describe the learning of rectangle area based on process standard NCTM that believed can help student understanding. The learning process is done through five phases that each using Student Worksheet. The research yields: (1) the increasing of student activities quality from 85% (in the first cycle) to 90% (in the second cycle), (2) the raising of student understanding from 73.5% (in the first cycle) to 82.5% (in the second cycle), and (3) good response from students.